Implementation of axis-aligned bounding box for opengl 3D virtual environment - Hamzah Asyrani Bin Sulaiman; Mohd Azlishah Othman; Mohamad Zoinol Abidin Abd. Aziz; Abdullah Bade (Asian Research Publishing Network, 2015)
This paper describes a simple and straight forward implementation of Axis-Aligned Bounding-Box (AABB) for OpenGL 3-Dimensional (3D) virtual environment for games and simulation purpose. The implementation of AABB is conducted in OpenGL graphic library version 1.2 with C++ programming language by using Visual C++. The implementation could help young and begineer computer graphics student to master the implementation of basic Bounding-Volume (BV) for collision detection and other fields with related to the Axis-Aligned Bounding-Box (AABB).